Nanoscale analysis of laser-induced surface relief gratings on azo-copolyimide films before and after gold coating. (December 2018) - Sava, Ion; Stoica, Iuliana; Mihaila, Ilarion; Pohoata, Valentin; Topala, Ionut; Stoian, George; Lupu, Nicoleta
Abstract: Free-standing, transparent, flexible films of aromatic azo-copolyimides based on benzophenonetetracarboxylic dianhydride and a mixture of 2, 2-bis3-amino-4-[(p-oxyalkyloxy–p'-methyl) azobenzene]-phenylene-hexafluoropropane (0.25mol) and 4, 4'-diamino-3, 3'dimethyldiphenylmethane (0.75mol) were studied with regard to their nanostructuring capacity and their ability to bear a load. Uniform and orientated surface relief gratings were obtained irrespective of pulses number (10 or 100), using a laser field with an energy density of 45 mJ/cm 2 . For the targeted applications, such as metallic reflective gratings, preliminary gold deposition tests were performed on the resulting nanostructures, gold being preferred due to its high optical performance. Atomic force microscopy and high-resolution scanning electron microscopy were used for complex characterization of the resulted structured surfaces, before and after gold coating. Highlights: Well-defined SRG were photo-induced on azo-copolyimides films to be used as support for subsequent metal deposition. The impact of copolymer conformation and UV laser irradiation conditions on the AFM 3D surface parameters was evaluated. Preliminary gold deposition tests were performed on the resulted nanostructures. Gold was preferred due to its high optical performance. SEM observations described the uniformity of the gold coatings for applications, such as metallic reflective gratings.